P050 Sexual health london online testing: a review of service users and outcomes. (14th July 2019) - Tittle, Victoria; Alston, Tim; Kinsella, Ryan; Jones, Sophie; Day, Sara; Asboe, David
Abstract : Background: Sexual Health London (SHL) provides online asymptomatic sexual health screen, channelling patients away from clinic attendances. We present data from commencement on the 8 th January to 31 st October 2018 from this service. Methods: Descriptive analysis of routine data from registered users, including general demographics, service metrics of test kits (including nuclear acid amplification testing of Chlamydia and Gonorrhoea and/or blood serology), infection results and outcomes of kits (returned by 18 th January 2019). Results: 82, 806 registered users ordered 81, 542 kits. 80.3% (n=65, 460/81, 542) kits were returned from 51, 039 unique users. Proportion of sufficient samples in return kits: blood samples = 77.24% (n=50482/65361), vaginal samples = 99.41% (n=38312/38541) and urine samples = 99.15% (n=26595/26822). Median age 27 years old (range 16–99). Sex and sexual orientation demographics of unique users (n): Heterosexual: female = 54% (27560), male = 27.13% (13848), trans* = 0.05% (24) Homosexual: female = 0.45% (232), male = 11.56% (5898), trans* = 0.03% (14) Bisexual: female = 4.29% (2190), male = 2.41% (1231), trans* = 0.08% (42) Reactive results from sufficient samples (numerator/denominator): Chlamydia 4.39% (2850/64907), Gonorrhoea 1.12% (726/64907), HIV 0.35% (173/49889), Syphilis 0.58% (283/48692), Hepatitis B 0.73% (n=69/9430) and Hepatitis C 0.56 (n=54/9635). 100% of patients with a reactive HIV result have been contacted by a health advisor. 119 patients were considered 'low level' or could not be confirmed due to low sample volume. Of 54 'high level' reactive results, 32 were true positives and 18 patients were new positive patients. Median time (days) from requesting kit to kit testing was 9 days (range 1- 280 days). 99.3% of reactive results were communicated within three days of receiving the sample. 97.2% (n=4454) of reactive Chlamydia results were confirmed to have transferred care to a clinic. Conclusion: These results provide an indication of service usage and outcomes of sexual health testing using online services. Disclosure: No significant relationships.